HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA DENGAN PRESTASI BELAJAR IPS SISWA SMPN 4 PALANGKA RAYA - Ubut Ubut (JURNAL SOCIUS, 2014)
The research aims to find out description of parents economic and social status students achievement. This research is based on quantitative approach; the population is all students of SMPN in Sebangau district, coming from three schools. The sample is all students of SMPN 4 Palangkaraya. As the procedure, data collection used questionaire to abtain the students’ social and economic status; test is used to measure the students’ achievement in social science subject. The test is multiple choice. The data analysis is based on SPSS and the formula is Spearman correlation. The research result  states that the parents’ social and economic status of the students are different. The result test says that students’ achievement are considered good. It can be concluded that there is no correlation between Parents’ Economic and Social Status and Student’ achievement. In a word, the hypothesis is rejected.Key words:  Economic and Social  Status,  Achievement, and Correlation